PENGARUH DISIPLIN KERJA DAN MOTIVASI KERJA TERHADAP KINERJA KARYAWAN PADA KANTOR JASA SURVEYOR KADASTER BERLISENSI (KJSKB) IHSAN PAKAYA SAMPIT - Deky Prasetyo (Eqien - Jurnal Ekonomi dan Bisnis, 2022)
The title of this research is the Influence of Work Discipline and Work Motivation on Employee Performance at the Licensed Cadastre Surveyor Service Office (KJSKB) Ihsan Pakaya Sampit. The population in this study were employees of the Licensed Cadastre Surveyor Service Office (KJSKB) Ihsan Pakaya. This study uses saturated sampling, the sample in this study as many as 35 employees. The data were tested using validity test, reliability test, hypothesis testing and research data analysis using descriptive analysis, multiple linear regression analysis, correlation coefficient analysis and analysis of determination. Based on the results of hypothesis testing in this study, the t-test for the Work Discipline variable (X1) is tcount 4.444> ttable 2.03693 and the significant level is 0.000 <0.05, then H0 is rejected and Ha is accepted. This means that there is a significant influence between Work Discipline on employee performance. While the t-test for the variable of Work Motivation (X2) is tcount 4.624> ttable 2.03693 and a significant level of 0.000 <0.05, then H0 is rejected and Ha is accepted, meaning that there is a significant influence between work motivation on employee performance. Then for the f-test, namely fcount 45.223> ftable 3.29 and a significant level of 0.000 <0.05, it means that there is a simultaneous influence of work discipline and work motivation on the performance of the employees of the Ihsan Pakaya Sampit Licensed Cadastre Surveyor Service Office (KJSKB). The number r of 0.859 shows the relationship/correlation between employee performance and the independent variable is strong (Significant). R Square of 0.739 means that 73.9% of the Employee Performance variable (Y) can be explained by the Work Discipline (X1) and Work Motivation (X2) variables. While the remaining 26.1% is influenced by other variables not included in this study such as Organizational Culture, Compensation and so on. Based on the results of multiple linear regression, the equation Y = 0.425 + 0.501 (X1) + 0.459 (X2) means that the score / constant value (α) indicates that if there is no increase in the Work Discipline and Work Motivation variables, the Employee Performance value is 0.425. And each addition of one score/value of the Work Discipline variable gives an increase of 0.501 to Employee Performance with the condition that X2 is fixed and each additional score/value of the Work Motivation variable gives an increase of 0.459 to Employee Performance with a fixed X1.